Use of alkali activated high-calcium fly ash binder for kaolin clay soil stabilisation: Physicochemical evolution. (20th March 2019) - Coudert, Elodie; Paris, Michael; Deneele, Dimitri; Russo, Giacomo; Tarantino, Alessandro
Highlights: Study of binder for soil stabilization based on fly ash (FA) alkaline activation. Different proportion of kaolin are progressively added as model soil. Calcium-rich phase of FA governs the system reactivity. The thenardite formation raises the question of durability of such stabilised material. Abstract: This study addresses the use of alkali activated high-calcium fly ash-based binder to improve engineering characteristics of soft clay-rich soils as an alternative to common stabilisers. The physico-chemical reaction sequence has been investigated by considering the binder alone and the binder mixed with kaolin. An insight into the reactivity evidenced that calcium-containing phases derived from high-calcium fly ash represent the reactive phases and, hence, pozzolanic activity is the dominant process. New compounds are formed, thenardite Na2 SO4 and an amorphous silicate consisting of chains combined with calcium probably incorporating three-dimensional four-fold aluminium environments.